2006
DOI: 10.1016/j.cardiores.2006.02.028
|View full text |Cite
|
Sign up to set email alerts
|

IKr contributes to the altered ventricular repolarization that determines long-term cardiac memory

Abstract: A transcriptionally induced change in epicardial I(Kr) contributes to the altered ventricular repolarization that characterizes CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 30 publications
1
34
0
Order By: Relevance
“…In animal experiments using long-term asynchronous activation by ventricular pacing or LBBB, several changes in ionic membrane currents have been observed, including changes in I CaL (40), I to (62), I Kr , and I Ks (37). In addition to changes in I CaL and calcium handling, Aiba et al (2) observed differences in several potassium currents, including I K , I Kl , and I to in their DHF model.…”
Section: Discussionmentioning
confidence: 95%
“…In animal experiments using long-term asynchronous activation by ventricular pacing or LBBB, several changes in ionic membrane currents have been observed, including changes in I CaL (40), I to (62), I Kr , and I Ks (37). In addition to changes in I CaL and calcium handling, Aiba et al (2) observed differences in several potassium currents, including I K , I Kl , and I to in their DHF model.…”
Section: Discussionmentioning
confidence: 95%
“…1). Changes in ARI in the intramural and subendocardial layers during AVS were presumably caused by an increase in the current density (I Ks ) [4] and inversion of the current gradient (I Kr ), respectively [5]. Left ventricular apical myocardium possesses no transmural heterogeneity of ARI in supraventricular rhythm and in AVS.…”
Section: Resultsmentioning
confidence: 99%
“…1, 46, 16 Moreover, cardiac memory provides a useful framework for understanding the evolution of remodeling because the pacing used to induce memory initiates two different yet complimentary processes. While long-term cardiac memory is the result of transcriptional changes of ion channels and Cx43, 4, 5, 25, 26 short-term memory has been proposed to result from ion channel trafficking initiated by altered myocardial stretch-induced synthesis and release of angiotensin II. 7,8 In this study, we demonstrated in intact animals that the internalization of I to channel subunits initiated by the binding of angiotensin II to the AT1R previously shown in single cell studies contributes to the induction of short-term cardiac memory and this internalization process uses a microtubule-mediated pathway.…”
Section: Discussionmentioning
confidence: 99%